The potential of fallow management to promote steppe bird conservation within the next EU Common Agricultural Policy reform. Issue 7 (14th May 2021) - Sanz‐Pérez, Ana; Sardà‐Palomera, Francesc; Bota, Gerard; Sollmann, Rahel; Pou, Nuria; Giralt, David
Abstract: Agricultural intensification promoted by the European Common Agricultural Policy (CAP) has driven the decline of farmland and steppe bird populations. Policy tools to improve the environmental performance of the CAP—including Agri‐Environmental Schemes (AES) and Greening—have often failed, and the new EU agricultural reform (CAP post‐2020) offers a new opportunity to integrate effective measures addressing farmland bird declines. Fallow land and its management have proven beneficial for endangered steppe bird species by providing good quality habitat, and therefore has potential to become an effective conservation measure. We used a Hierarchical Distance Sampling community model to evaluate the ability of different conservation regimes to increase the abundance of 37 bird species including endangered steppe birds and other farmland birds in 13, 309 ha of fallow land in north‐eastern Spain. The conservation regimes were based on different management prescriptions associated with AES, Greening and a local conservation measure promoting extensive fallow management targeting seven steppe bird species (Targeted Fallow Management, TFM). The positive effect of conservation measures increased as their design was more targeted to specific species. TFM increased the abundance of target and other farmland species, while AES and Greening had either no effect or negative effects on bird abundance, respectively. Effects of other Greening conservation measures related to landscape heterogeneity such as crop richness and field size were variable across the community. Policy implications . The success of Targeted Fallow Management as a conservation tool—in contrast to Agri‐Environmental Schemes and Greening—highlights the value of applying 1–2 agricultural practices just before the breeding season in fallows situated in optimal locations for target steppe bird species, to increase the abundance of these and other farmland bird species. We translate our findings into specific guidelines that we recommend including within the new eco‐schemes and AES present in the CAP post‐2020. Abstract : The success of Targeted Fallow Management as a conservation tool—in contrast to Agri‐Environmental Schemes and Greening—highlights the value of applying 1–2 agricultural practices just before the breeding season in fallows situated in optimal locations for target steppe bird species, to increase the abundance of these and other farmland bird species. We translate our findings into specific guidelines that we recommend including within the new eco‐schemes and AES present in the CAP post‐2020.